Understanding migration: Challenges pending - Espiro, María Luz; Munck, Ronaldo (Revista de Estudios Globales. Análisis Histórico y Cambio Social, 2025)
The introduction to the special issue Migrations and Globalizations: Transdisciplinary and Transnational Perspectives highlights the need to understand migration as a complex, multidimensional, and dynamic process embedded within broader social, political, and economic transformations. Drawing on Sayad’s concept of migration as a “total social fact,” the authors emphasize that mobility cannot be reduced to linear models or simplistic explanations. Migration reshapes both individual lives and the societies of origin and destination, requiring analytical approaches that integrate economic, political, cultural, religious, gendered, and environmental dimensions. Recent crises, such as the 2008 financial downturn and the Covid-19 pandemic, have exacerbated global inequalities and intensified migration controls, reinforcing discourses of crisis and exclusion. Nonetheless, migration endures as a field of agency, negotiation, and resistance, where migrants actively challenge restrictive policies and reshape mobility landscapes. The authors stress the importance of adopting a transnational lens that moves beyond state-centered frameworks and methodological nationalism, incorporating the experiences of both migrants and those who remain connected through transnational social fields. They also call for decentering migration studies from Global North perspectives to acknowledge the importance of South-South mobility, frequently overlooked in mainstream scholarship. Furthermore, the authors advocate overcoming disciplinary fragmentation by fostering transdisciplinary dialogue and combining macro-level structural analyses with micro-level explorations of migrant agency and lived experience. The intersectional approach is presented as fundamental to understanding the multiple and overlapping inequalities that shape migration trajectories, with particular attention to gender, ethnicity, class, and generation. This special issue brings together contributions from various disciplines, addressing labour migration, climate change, religion, South-South mobility, highly skilled female migrants, refugee movements, digital nomadism, and regional governance. Collectively, these articles enrich academic debate, offering critical insights into the complexities of contemporary human mobility in a context marked by growing inequalities and global transformations.